Rare detection of bordetella pertussis pertactin-deficient strains in Argentina - Carriquiriborde, Francisco Pablo (2019)
Pertussis resurgence had been attributed to waning vaccine immunity and Bordetella pertussis adaptation to escape vaccine-induced immunity. Circulating bacteria differ genotypically from strains used in production of pertussis vaccine. Pertactin-deficient strains are highly prevalent in countries that use acellular vaccine (aP), suggesting strong aP-imposed selection of circulating bacteria. To corroborate this hypothesis, systematic studies on pertactin prevalence of infection in countries using whole-cell vaccine are needed. We provide pertussis epidemiologic data and molecular characterization of B. pertussis isolates from Buenos Aires, Argentina, during 2000-2017. This area used primary vaccination with whole-cell vaccine. Since 2002, pertussis case incidences increased at regular 4-year outbreaks; most cases were in infants <1 year of age. Of the B. pertussis isolates analyzed, 90.6% (317/350) contained the ptxP3-ptxA1-prn2-fim3-2 allelic profile. Immunoblotting and sequencing techniques detected only the 2 pertactin-deficient isolates. The low prevalence of pertactin-deficient strains in Argentina suggests that loss of pertactin gene expression might be driven by aP vaccine.